Neonatal outcomes of late preterm and early term birth - Machado, Luis C.; Passini, Renato; Rosa, Izilda R.; Carvalho, Heraclito B. [UNESP] (Elsevier B.V., 2014)
Objective: To compare neonatal deaths and complications in infants born at 34-36 weeks and six days (late preterm: LPT) with those born at term (37-41 weeks and six days); to compare deaths of early term (37-38 weeks) versus late term (39-41 weeks and six days) infants; to search for any temporal trend in LPT rate. Study design: A retrospective cohort study of live births was conducted in the Campinas State University, Brazil, from January 2004 to December 2010. Multiple pregnancies, malformations and congenital diseases were excluded. Control for confounders was performed. The level of significance was set at p < 0.05. Results: After exclusions, there were 17,988 births (1653 late preterm and 16,345 term infants). A higher mortality in LPT versus term was observed, with an adjusted odds ratio (OR) of 5.29 (p < 0.0001). Most complications were significantly associated with LPT births. There was a significant increase in LPT rate throughout the study period, but no significant trend in the rate of medically indicated deliveries. A higher mortality was observed in early term versus late term infants, with adjusted OR: 2.43 (p = 0.038). Conclusion: LPT and early term infants have a significantly higher risk of death. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Preterm labor; Early neonatal mortality; Neonatal mortality; Infant mortality; High-risk pregnancy